2014
DOI: 10.1517/13543776.2014.959491
|View full text |Cite
|
Sign up to set email alerts
|

Acylhydrazone derivatives: a patent review

Abstract: In the last century, only six patents disclosing NAH derivatives for therapeutic purposes were published, and only in 2010, this subunit started receiving some real attention regarding its therapeutic potential. In this review, the Brazilian and Chinese Universities were identified as the major patent applicants, especially for drug candidates for the treatment of chronic pain, inflammatory disorders and cancer. The NAH subunit is very versatile both from synthetic and medicinal chemistry point of view. This f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…STK899704 has an acylhydrazone moiety known as a useful scaffold for drug development, especially for anticancer therapy due to its antimitotic activity [3842]. Further analyses showed that STK899704 strongly induces the accumulation of mitotic cells in a concentration-dependent and reversible manner (Fig 2A, 2B and 2D).…”
Section: Discussionmentioning
confidence: 99%
“…STK899704 has an acylhydrazone moiety known as a useful scaffold for drug development, especially for anticancer therapy due to its antimitotic activity [3842]. Further analyses showed that STK899704 strongly induces the accumulation of mitotic cells in a concentration-dependent and reversible manner (Fig 2A, 2B and 2D).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that acylhydrazone derivatives are rapidly metabolized, this motif is encountered in several approved drugs (e.g., nifuroxazide and dantrolene) [24] and drug candidates [25][26][27]. The facile synthetic availability of acylhydrazone derivatives, which allows furnishing congeneric series of compounds with distinct physico-chemical properties and bioactivities, makes it a promising scaffold in the drug discovery field [28][29][30]. Herein, we describe the synthesis of novel derivatives and the determination of their in vitro and in cellulo ability to bind to G4 of EBNA1 mRNA, as well as their effect on NCL-mediated GArdependent limitation of EBNA1 expression and antigen presentation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Many of these compounds were patented in this respect. 7 Monohydrazide derivatives of carbonic and thiocarbonic acid, semicarbazide and thiosemicarbazide, respectively react with N-heteroaromatic carbonyl compounds giving (thio)semicarbazones -molecules well described as tridentate NNO(S) chelators and ribonucleotid reductase (RR) inhibitory agents. 8 RR plays a fundamental role in the critical early events involved in tumor promotion and activity of this enzyme is tightly linked to the neoplastic expression state and is currently one of the main targets for DNA inhibition by anticancer agents.…”
Section: Introductionmentioning
confidence: 99%